The Emergence and Initial Impact of Stony Coral Tissue Loss Disease (SCTLD) in the United States Virgin Islands - Brandt, Marilyn E.; Ennis, Rosmin S.; Meiling, Sonora S.; Townsend, Joseph; Cobleigh, Kathryn; Glahn, Adam; Quetel, Jason; Brandtneris, Viktor; Henderson, Leslie M.; Smith, Tyler B. (Frontiers in Marine Science, 2021)
Coral communities in the Caribbean face a new and deadly threat in the form of the highly virulent multi-host stony coral tissue loss disease (SCTLD). In late January of 2019, a disease with signs and characteristics matching that of SCTLD was found affecting a reef off the coast of St. Thomas in the U.S. Virgin Islands (USVI). Identification of its emergence in the USVI provided the opportunity to document the initial evolution of its spatial distribution, coral species susceptibility characteristics, and its comparative impact on coral cover at affected and unaffected coral reef locations. Re-assessments at sentinel sites and long-term monitoring locations were used to track the spread of the disease, assess species affected, and quantify its impact. The disease was initially limited to the southwest of St. Thomas for several months, then spread around the island and to the neighboring island of St. John to the east. Differences in disease prevalence among species were similar to reports of SCTLD from other regions. Highly affected species included Colpophyllia natans, Eusmilia fastigiata, Montastraea cavernosa, Orbicella spp., and Pseudodiploria strigosa. Dendrogyra cylindrus and Meandrina meandrites were also highly affected but showed more variability in disease prevalence, likely due to initial low abundances and the rapid loss of colonies due to disease. Siderastrea spp. were less affected and showed lower prevalence. Species previously reported as unaffected or data deficient that were found to be affected by SCTLD included Agaricia spp., Madracis spp., and Mycetophyllia spp. We also observed multi-focal lesions at SCTLD-affected sites on colonies of Porites astreoides, despite that poritids have previously been considered low or not susceptible to SCTLD. Loss of coral cover due to acute tissue loss diseases, which were predominantly SCTLD, was significant at several monitoring locations and was more impactful than previous mass bleaching events at some sites. There are no signs that the USVI SCTLD outbreak is abating, therefore it is likely that this disease will become widespread across the U.S. Caribbean and British Virgin Islands in the near future.